The Influence of Price, Promotion, and Brand Image on Purchase Decisions of Red Sugar at UD Nira Sari, Kediri Regency - YUKI MAHENDRA, RAFAEL (Universitas Nusantara PGRI Kediri, 2025)
This research aims to address the gap by analyzing the influence of price, promotion, and brand image on purchasing decisions for palm sugar at UD Nira Sari in Kediri Regency. The study adopted a research design grounded in quantitative methods a survey method to collect data from 40 respondents. Multiple regression analysis is applied to investigate the connection between the independent variables (price, promotion, and brand image) and the dependent variable (purchasing decisions). The findings reveal that price, promotion, and brand image significantly influence decisions related to buying for palm sugar at UD Nira Sari. Among these variables, brand image has the most substantial impact, followed by promotion and price. Collectively, these variables explain 62.7% of the variation in consumer purchasing decisions. This study contributes to the literature by demonstrating the integrated impact of price, promotion, and brand image on purchasing decisions, particularly in the context of a local industry like UD Nira Sari. It highlights the significance of taking these factors into account together to achieve a thorough understanding of consumer behavior regarding palm sugar products. The findings provide actionable insights for business practitioners, especially in the local palm sugar industry, to improve consumer purchasing decisions. This can be achieved by prioritizing brand image improvements, designing effective promotional strategies, and setting competitive and value-oriented pricing. These implications are particularly relevant for business owners like UD Nira Sari and marketing managers in developing consumer-focused strategies. This study is limited to the demographic scope of consumers at UD Nira Sari in Kediri Regency, this may restrict the ability to generalize the findings to other contexts. regions. Future research could expand the respondent coverage and explore additional variables, such as consumer trust or digital marketing strategies, to enrich the analysis.